First-in-human trial of the post-exposure tuberculosis vaccine H56:IC31 in Mycobacterium tuberculosis infected and non-infected healthy adults. Issue 33 (7th August 2015) - Luabeya, Angelique Kany Kany; Kagina, Benjamin M.N.; Tameris, Michele D.; Geldenhuys, Hennie; Hoff, Soren T.; Shi, Zhongkai; Kromann, Ingrid; Hatherill, Mark; Mahomed, Hassan; Hanekom, Willem A.; Andersen, Peter; Scriba, Thomas J.; et al.
Abstract: Background: H56:IC31 is a candidate tuberculosis vaccine comprising a fusion protein of Ag85B, ESAT-6 and Rv2660c, formulated in IC31 adjuvant. This first-in-human, open label phase I trial assessed the safety and immunogenicity of H56:IC31 in healthy adults without or with Mycobacterium tuberculosis ( M.tb ) infection. Methods: Low dose (15 μg H56 protein in 500 nmol IC31) or high dose (50 μg H56, 500 nmol IC31) vaccine was administered intramuscularly thrice, at 56-day intervals. Antigen-specific T cell responses were measured by intracellular cytokine staining and antibody responses by ELISA. Results: One hundred and twenty-six subjects were screened and 25 enrolled and vaccinated. No serious adverse events were reported. Nine subjects (36%) presented with transient cardiovascular adverse events. The H56:IC31 vaccine induced antigen-specific IgG responses and Th1 cytokine-expressing CD4 + T cells. M.tb -infected vaccinees had higher frequencies of H56-induced CD4 + T cells than uninfected vaccinees. Low dose vaccination induced more polyfunctional (IFN-γ + TNF-α + IL-2 + ) and higher frequencies of H56-specific CD4 + T cells compared with high dose vaccination. A striking increase in IFN-γ-only-expressing CD4 + T cells, displaying a CD45RA − CCR7 − effector memory phenotype, emerged after the second high-dose vaccination in M.tb -infected vaccinees. TNF-α + IL-2 + H56-specific memory CD4 + T cells were detected mostly after low-dose H56 vaccination in M.tb -infected vaccinees, and predominantly expressed a CD45RA − CCR7 + central memory phenotype. Our results support further clinical testing of H56:IC31.